Microbial-Mediated Plant Growth Promotion and Pest Suppression Varies Under Climate Change - Zytynska, Sharon E.; Eicher, Moritz; Rothballer, Michael; Weisser, Wolfgang W. (Frontiers in Plant Science, 2020)
Climate change is altering the dynamics of crop pests and diseases resulting in reduced crop yields. Using beneficial soil bacterial to increase crop health is a quickly developing area in sustainable agriculture, but it is unknown if climate change or interactions with other species could alter their effect. The plant growth-promoting rhizobacterium Acidovorax radicis N35 is known to increase barley (Hordeum vulgare) plant growth under laboratory conditions, and we tested the stability of the plant-bacterial interactions when exposed to elevated carbon dioxide (CO2) and ozone (O3) levels while infesting the aboveground leaves with cereal aphids (Sitobion avenae) and the soil with beneficial earthworms. Acidovorax radicis N35 increased plant growth and reduced insect growth – with greatest effect in a high-stress elevated O3 environment, but reduced effects under elevated CO2. Earthworms promoted both plant and insect growth, but inoculation with A. radicis N35 alleviated some of the earthworm-mediated increase in pest abundance, particularly in the ambient environment. The consistency of these beneficial effects highlights the potential of exploiting local species interactions for predicting and mitigating climate change effects in managed systems. We conclude that microbial bioprotectants have high potential for benefiting agriculture via plant-growth promotion and pest suppression.